Respostas termorregulatórias ao exercício agudo e ao treinamento físico: participação do núcleo paraventricular do hipotálamo - Juliana Bohnen Guimaraes (2012)
Core body temperature is a result from the balance between heat production and heat dissipation, and it is regulated within a narrow rangeregardless of changes in ambient temperature. Projections from the POA to the hypothalamus and also physiological evidences indicate that paraventricular nucleus of hypothalamus (PVN) is involved in central pathways that modulate sympathetic activity to organs thermoeffectors. In addition, PVN is activated during heat stress and during exercise with high intensity. On the other hand, studies that used electrolytic lesions into the PVN contradict the indication of this nucleus in the participation of thermoregulation. Thus, one of the aims of this study was to investigate the involvement of the PVN on thermoregulation and performance, and verify whether the exercise with moderate intensity until fatigue induces the activation of the nucleus and its relation to thermoregulatory adjustments and to performance. In this study, the results demonstrated that the expression of c-Fos into the PVN was increased by exercise until fatigue, which is associated with heat storage rate and performance. Furthermore, electrolytic lesions, bilaterally, in the PVN attenuated heat dissipation and changing heat storage rate, which may have contribute to the reduction on performance. However, lesions into the PVN does not appear changing the pathways that activate behavioral mechanisms todefend core body temperature, since that the elevation of heat storage rate was centrally perceived, inducing the fatigue anticipation. From these results, we found that some adaptations induced by physical training could be mediated via dopamine in the PVN. Physical training promotesadaptive responses similar to those described by the increased availability of central dopamine. Thus, we hypothesized that exercise training could modify the dopaminergic system, specifically in the PVN, in association with performance and thermoregulatory changes, induced by exercise until fatigue. Physical training induced an increased heat dissipation, which was verified in vivo, by anticipation of tail vasodilation, and in vitro, by increased caudal artery vascular reactivity. Furthermore, physical training increased and reduced D1 and D2 receptor expression, respectively, in the PVN, although no difference was found in dopamine concentration, its metabolite DOPAC, or in dopaminergic turnover in hypothalamus, hippocampus or POA. The dopamine and DOPAC concentration measured in the POA and hypothalamus were positively correlated with the heat storage / workload performed, only in trainedgroup. This result evidences that the changes in dopaminergic signaling in the PVN contributes to increased heat dissipation. Furthermore, D1 receptor expression in the PVN significantly correlated with time of exercise until fatigue, also evidencing the involvement of dopaminergic system on performance. Although these results indicate strong evidences of the participation of the dopaminergic system in the PVN on thermoregulation and performance, the direct function of the dopamine is still unclear. Thus, the effect of D1 receptor blockade in the PVN on thermoregulatory and cardiovascular adjustments was evaluated during heat stress, a similar hyperthermic condition to the increase of core body temperature, however with the possibility of measuring the direct sympathetic activity. The blockade of D1 receptor in the PVN attenuated the renal sympathetic nerve activity, suggesting an attenuation of renalvasoconstriction and consequently reduced blood flow redistribution toperiphery. This response could be checked by the reduced tail vasodilation and heat dissipation, and also attenuation on mean arterial pressure. However, heart rate was not different between groups, suggesting a possible change on barorreflex stimulus in rats with D1 receptors blocked in PVN. Our data indicate that dopaminergic system in the PVN participate on thermal regulation during the exercise, which can determine performance and influence some adaptations induced by physical training. Furthermore, exercise increases neuronal activation in the PVN, which is crucial for the thermal adjustments and performance.